Pengaruh Kepemimpinan Dan Manajemen Konflik Kepala Sekoah Terhadap Motivasi Kerja Guru - Siti Nurjannah; Tri Yuni Hendrowati; Arman (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyse the influence of principal leadership and conflict management on teachers’work motivation. A quantitative approach is used with a type of correlational research. Data wascollected through a questionnaire with the Likert scale, followed by tests of validity, reliability,normality, and linearity. The study was conducted on 141 high school teachers in Kotaagung Districtwith a sample taken proportionally using the Slovin formula. The results of the study show that theleadership of school principals has a significant positive influence on teachers’ work motivation witha contribution of 25.1%. Conflict management also had a significant positive effect with a contributionof 16.6%. However, when tested together, leadership and conflict management did not show asignificant influence on teachers’ work motivation, indicating that there were other factors that weremore dominant in influencing work motivation. This research makes a theoretical contribution tothe development of literature on the role of transformational leadership and conflict management inincreasing teachers’ work motivation. Practically, these results can be a reference for school principalsand policymakers to create a conducive work environment through effective leadership and conflictmanagement.